The Effect of the Electronic Health Record on Interprofessional Practice: A Systematic Review - Robertson, Samantha T.; Rosbergen, Ingrid C.M.; Burton-Jones, Andrew; Grimley, Rohan S.; Brauer, Sandra G. (Applied Clinical Informatics, 2022)
Background Interprofessional practice and teamwork are critical components to patient care in a complex hospital environment. The implementation of electronic health records (EHRs) in the hospital environment has brought major change to clinical practice for clinicians which could impact interprofessional practice.Objectives The aim of the study is to identify, describe, and evaluate studies on the effect of an EHR or modification/enhancement to an EHR on interprofessional practice in a hospital setting.Methods Seven databases were searched including PubMed, Scopus, Web of Science, CINAHL, Cochrane, EMBASE, and ACM Digital Library until November 2021. Subject heading and title/abstract searches were undertaken for three search concepts: “interprofessional” and “electronic health records” and “hospital, personnel.” No date limits were applied. The search generated 5,400 publications and after duplicates were removed, 3,255 remained for title/abstract screening. Seventeen studies met the inclusion criteria and were included in this review. Risk of bias was quantified using the Quality Assessment Tool for Studies with Diverse Designs. A narrative synthesis of the findings was completed based on type of intervention and outcome measures which included: communication, coordination, collaboration, and teamwork.Results The majority of publications were observational studies and of low research quality. Most studies reported on outcomes of communication and coordination, with few studies investigating collaboration or teamwork. Studies investigating the EHR demonstrated mostly negative or no effects on interprofessional practice (23/31 outcomes; 74%) in comparison to studies investigating EHR enhancements which showed more positive results (20/28 outcomes; 71%). Common concepts identified throughout the studies demonstrated mixed results: sharing of information, visibility of information, closed-loop feedback, decision support, and workflow disruption.Conclusion There were mixed effects of the EHR and EHR enhancements on all outcomes of interprofessional practice, however, EHR enhancements demonstrated more positive effects than the EHR alone. Few EHR studies investigated the effect on teamwork and collaboration.
Keywords: electronic health records; interdisciplinary teams; interprofessional practice; hospitals